Comparison of Phytochemicals, Antioxidant, and Antimicrobial Activities of in Vitro Propagated and Wild Grown Potentilla Nepalensis, an Endemic Medicinal Plant from North Western Himalayas. Issue 3 (3rd July 2022) - Sharma, Subhash; Kumar, Vikas; Attri, Chandrika; Sourirajan, Anuradha; Dev, Kamal
ABSTRACT: A reliable protocol for in vitro propagation of Potentilla nepalensis was developed and the phytochemical, antioxidant, and antimicrobial effects of in vitro propagated and wild grown P. nepalensis plants were compared. Leaves of P. nepalensis used as explants were cultured on conventional Murashige and Skoog (MS) medium supplemented with different concentrations and combinations of plant growth regulators. Optimum sterilization conditions were achieved by using 0.04% Bavistin for 10 min, 0.04% sodium hypochlorite for 1 min, and 0.04% mercuric chloride for 1 min and the optimum media composition for callus generation was MS minerals containing ammonium nitrate (165 mg L −1 ), calcium chloride (44 mg L −1 ), and growth regulators IBA (20 mg L −1 ), and BAP (4 mg L −1 ). The phenolic and flavonoid content were higher in wild grown plant (TPC-21.21 ± 0.54 mg g −1 GAE; TFC-4.24 ± 0.17 mg g −1 RE) compared to in vitro propagated P. nepalensis (TPC-3.55889 ± 0.72 mg g −1 GAE; TFC-0.33 ± 0.07 mg g −1 RE). Although the antioxidant activity was high in wild grown plant (IC50 -235 ± 92.120 µg mL −1 ) than in vitro propagated (IC50 -682.989 ± 57.118 µg mL −1 ), the antimicrobial properties for bacterial and fungal pathogens were similar.